GE_GERICHTE P/15674/2016 vom 29. Oktober 2020 - GE Cour de justice (2020)
IN DUBIO PRO REO;DOL ÉVENTUEL;LESIONS CORPORELLES SIMPLES AGGRAVEES;LÉSION CORPORELLE GRAVE;LÉGITIME DÉFENSE;TORT MORAL | CPP.110; CP.22; CP.123.al2; CP.122; CP.15; CP.16; CPP.126; CC.47; CC.49; CC.44